ANALISIS USER INTERFACE DALAM APLIKASI MOBILE LIBRARY IPUSNAS - Bekti Mar’atun Aisyiyah (Jurnal Pustaka Ilmiah, 2019)
This study to determine the application of the user interface in the IPusnas mobile library application. Analysis of the application of the user interface in this mobile library application uses 10 components, namely conectivity, directional, informative , interactivity, user friendliness, comprehensiveness, continuity, personalization, and internal (internal). In this article the research method uses a kaulitatif descriptive approach. Where from this study it can be concluded that the application of IPusnas makes it easy for users to search and read e-Book. This application is flexible because users can take advantage of this IPusnas application anywhere and anytime according to their wishes and this makes the IPusnas application easy to use. However, it is necessary to develop applications again to further optimize the appearance of the IPusnas application. In addition, the Perpustakaan Nasional (Perpusnas) needs to promote the Ipusnas mobile library application that has been made to the general public, so that applications can be fully utilized.